2023
DOI: 10.1098/rspb.2023.0316
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of artefacts made of giant sloth bones in central Brazil around the last glacial maximum

Abstract: The peopling of the Americas and human interaction with the Pleistocene megafauna in South America remain hotly debated. The Santa Elina rock shelter in Central Brazil shows evidence of successive human settlements from around the last glacial maximum (LGM) to the Early Holocene. Two Pleistocene archaeological layers include rich lithic industry associated with remains of the extinct giant ground sloth Glossotherium phoenesis . The remains include thousands of osteoderms (i.e. dermal bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 67 publications
4
8
0
Order By: Relevance
“…Although explicit analyses of body size evolution in freshwater turtles are lacking, until now, no gigantic representative of this ecological group was known after the Miocene [ 5 ]. The Late Pleistocene Peltocephalus maturin fills this gap, hinting at the possibility that it was coeval with the early peopling of South America [ 42 ]. It has been suggested that extinctions of giant tortoises in the Late Pleistocene to Early Holocene, particularly in Australia and South America, followed a similar pattern to those of herbivorous mammals and other megafauna, and were directly related to human overexploitation [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although explicit analyses of body size evolution in freshwater turtles are lacking, until now, no gigantic representative of this ecological group was known after the Miocene [ 5 ]. The Late Pleistocene Peltocephalus maturin fills this gap, hinting at the possibility that it was coeval with the early peopling of South America [ 42 ]. It has been suggested that extinctions of giant tortoises in the Late Pleistocene to Early Holocene, particularly in Australia and South America, followed a similar pattern to those of herbivorous mammals and other megafauna, and were directly related to human overexploitation [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers state there is sufficient evidence to support a very early peopling of the continent (*130,700 calibrated years before present, cal yr BP) [5,6]. However, most of the very early putative sites fall within the *33,000-19,000 cal yr BP time frame [2,[7][8][9][10]. Although all these proposals have received considerable criticism from those in favor of a more recent peopling process (post Last Glacial Maximum, <18,000 cal yr BP) [11][12][13][14][15][16], this growing evidence cannot be completely dismissed, especially if we consider the alternative of failed colonization processes.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we report the material used for the manufacture of a ~ 12,940 year old tubular bone bead from the La Prele Mammoth site in Converse County, Wyoming, USA. We suggest that this bead is among the oldest, if not the oldest, known ornament from the Americas with one possible exception 16 .…”
Section: Introductionmentioning
confidence: 83%